Strategy Development of Innovation Capability of Coffee SME Using Resource-based View Approach: Knowledge Sharing Perspective - Tinneke Hermina; Acep Abdul Basit; Muslim Alkautsar (UIN Sunan Gunung Djati, 2023)
The challenges of globalization in the SME sector are getting tougher. SMEs are required to innovate in order to be able to face the challenges of globalization. The purpose of this study is to identify the internal resources of Coffee SME to create innovation capabilities and to determine the effect of knowledge sharing on the innovation capabilities of Coffee SMEs in Garut Regency. This study uses the Mix Method. Qualitative method with Resource-Base View (RBV) approach based on knowledge sharing perspective. The quantitative method is implemented through distributing questionnaires. Data collected using a questionnaire were analyzed using a structural equation model - partial least squares (SEM-PLS). The unit of analysis is seven Coffee SMEs in Garut Regency which has the same character resemblance. The results of the qualitative research show that IKM Coffee in Garut Regency is at the level of competitive advantage. Competitive advantage in question can be seen in several aspects. First, Coffee SME is able to create innovation capabilities in coffee processing from post-harvest to ready-to-drink coffee, limited to various flavors and aromas, that are tacit knowledge. Second, Coffee SME is able to innovate on brands, solar dryer domes, video content as a marketing tool, and coffee processing SOPs that are explicit knowledge. However, Garut coffee SMEs have not been able to achieve a level of sustainable competitive advantage where tacit knowledge and explicit knowledge can be well organized. While the results of quantitative research show that knowledge sharing has a positive effect on innovation capability.